The Influence of the Application of Inquiry and Problem Based Learning Models on the Critical Thinking Ability of Students in 5th Grade Elementary School - Arifandi, Mufti; Kristin, Firosalia (Journal of Educational Sciences, 2020)
The research aimed to find out the influence of the application of inquiry learning and problem-based learning and model toward students’ critical thinking skills on the content of 5th-grade science lessons in elementary schools. Types of the research are a quasi-experiment with a nonequivalent control group design. The population of this research is the 5th-grade students of SDN 02 Salatiga as the experiment class and the 5th-grade students of SDN Ledok 07 Salatiga as the control class. The instrument used was an observation instrument and an instrument test. Research hypothesis test using independent sample t-test with a significance level of 5% (α - 0,05). The results showed that the observation instrument obtained a significance value of 0,002 which means 0,002 < 0,05 and the instrument test obtained a significance value of 0,000 which means 0,000 < 0,05, then both of these data are Ho=rejected and Ha=accepted. Thus, it can be concluded there is a significant difference between the critical thinking abilities of students who are given Inquiry learning models and students who are given a Problem-Based Learning model.